PENERAPAN METODE TANYA JAWAB DAN DISKUSI SERTA PERAN MEDIA PEMBELAJARAN DALAM MENGATASI MINIMNYA PARTISIPASI SISWA KELAS III SDN 13 MATARAM - Sagira, Adella; Nadiatullah, Asri; Hasanah, Baiq Madina; Darajat, Baiq Zakiya; Wirayani, Dende Fitria; Istiningsih, Siti (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe the implementation of the question-and-answer and discussion methods, as well as the role of instructional media in encouraging student engagement in the learning process. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the question-and-answer and discussion methods can increase student participation when combined with engaging learning media appropriate to the developmental stage of the children. The use of media such as number cards, visual aids, and educational videos helps create a more interactive and enjoyable learning atmosphere. However, challenges such as limited facilities, differences in student abilities, and time constraints remain obstacles. These findings indicate that interactive and contextual learning approaches have the potential to foster more equitable and meaningful student participation.